Case report: Cerebral sinus vein thrombosis in VEXAS syndrome - Zisapel, Michael; Seyman, Estelle; Molad, Jeremy; Hallevi, Hen; Mauda-Havakuk, Michal; Jonas-Kimchi, Tali; Elkayam, Ori; Eviatar, Tali (Frontiers in Medicine, 2024)
VEXAS syndrome (vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic) is a newly described hemato-inflammatory acquired monogenic entity, that presents in adulthood. One of the main features of VEXAS syndrome is a high venous thromboembolism (VTE) burden, with approximately 30%-40% experiencing lower extremity deep vein thrombosis and a lower incidence of pulmonary embolism at around 10%. To date, VEXAS syndrome has not been associated with rarer forms of VTE such as cerebral sinus vein thrombosis (CSVT) and Budd-Chiari syndrome, which are well-recognized vascular manifestations in Behcet's disease, another autoinflammatory vasculitic disease. Herein, we describe a case of acute severe extensive and fatal CSVT in a patient with VEXAS syndrome.The event occurred during a period of apparently quiescent inflammatory status while the patient was receiving tocilizumab and a low dose of glucocorticoids. Despite treatment with anticoagulation, high-dose glucocorticoids, endovascular thrombectomy, and intracranial pressure-lowering agents, the patient suffered severe neurologic damage and ultimately succumbed to the condition three weeks after the onset of CSVT.To the best of our knowledge, this is the first reported case of CVST in a patient with VEXAS syndrome.